2023
DOI: 10.3390/life13091839
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Yeasts, Antioxidant and Healing Properties of Henna Pre-Treated by Moist Heat and Molecular Docking of Its Major Constituents, Chlorogenic and Ellagic Acids, with Candida albicans and Geotrichum candidum Proteins

Sulaiman A. Alsalamah,
Mohammed Ibrahim Alghonaim,
Mohammed Jusstaniah
et al.

Abstract: Lawsonia inermis, known as henna, has traditionally been utilized in cosmetics and folk medicine because of their valuable health effects. A lack of information about the processes that increase or decrease release, as well as the biological activities of constituents of natural origin, is an important pharmacological problem. This investigation evaluates the influence of moist heat on the flavonoid and phenolic contents of henna powder and their biological activities. HPLC analysis reflected the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…They demonstrate antiinflammatory, antibacterial, and anti-yeast effects, possess antiallergic properties, stimulate collagen production, and provide protection against UVB radiation. [40,41]. All of these mentioned features make U. dioica extract a valuable cosmetic additive candidate.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrate antiinflammatory, antibacterial, and anti-yeast effects, possess antiallergic properties, stimulate collagen production, and provide protection against UVB radiation. [40,41]. All of these mentioned features make U. dioica extract a valuable cosmetic additive candidate.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the docking interaction tool was performed to compare between interaction of ellagic acid and chlorogenic acid with the crystal structures of pathogenic yeasts including C. albicans (4YDE) and G. candidum (4ZZT). The obtained results indicated that chlorogenic acid was more active with a docking score of −7.84379 kcal/mol, than ellagic acid with a docking score of −6.18615 kcal/mol (Alsalamah et al 2023). Recently, in silico studies on interaction of P. ostreatus active constituents with MCF-7 cancer cell line was documented (Mishra et al 2022).…”
Section: Antimicrobial Activity Of Cooked and Uncooked G Lucidum Extractmentioning
confidence: 92%
“…To detect flavonoids, a detector wavelength of 284 nm was used. The presence of standard constituents was necessary for the identification of constituents [27].…”
Section: Hplc Analysis Of Phenolic and Flavonoid Constituents Of Zygn...mentioning
confidence: 99%